Aromatherapy and Essential Oils: Strategies to Reduce Menopausal Symptoms - Sari, Fatmi Nirmala; Said, Mohamed Saifulaman Mohamed; Rashid, Norhashima Abd (Edujavare Publishing, 2025)
Menopause often triggers a variety of physiological and psychological discomforts such as hot flashes, anxiety, insomnia, and mood swings, significantly impacting women's quality of life. Many women seek natural alternatives to hormone replacement therapy, leading to increased interest in aromatherapy and essential oils as complementary treatments. This study aimed to analyze and synthesize scientific evidence regarding the effectiveness of aromatherapy and essential oils in alleviating menopausal symptoms. Using a literature review method, this study systematically reviewed studies published between 2000 and 2025 through databases including PubMed, ScienceDirect, Scopus, and Google Scholar. The results revealed that essential oils, particularly lavender, clary sage, peppermint, and geranium, show significant potential in improving emotional stability, sleep quality, and vasomotor regulation. Thematic content analysis demonstrated that aromatherapy influences mood and hormonal balance through neurochemical and physiological mechanisms related to the limbic system and endocrine function. Despite variations in methodology, the findings consistently support aromatherapy as a safe, non-invasive, and effective complementary therapy for menopausal women. This study contributes to holistic healthcare by strengthening the integration of evidence-based aromatherapy into women's health strategies while emphasizing the need for further standardized, long-term clinical trials.